Differences in levelFms-Like Tyrosine Kinase-1 (sFlt-1), soluble Endoglin (s-Eng), and Placental Growth Factor (PIGF) between Early Onset Preeclampsia and Late Onset Preeclampsia - Lita Nafratilova; Yusrawati Yusrawati; Irza Wahi (Journal of Midwifery, 2018)
Early Onset Preeclampsia (EO-PE) is preeclampsia that develops before 34 weeks 'gestation, caused by intrinsic factors, while Late Onset Preeclampsia (LO-PE) is preeclampsia that develops after 34 weeks' gestation due to extrinsic and maternal factors. There is an increased production of antiangiogenic factors (sFlt-1, s-Eng and PIGF) contribute to pathophysiology of preeclampsia.This study aims to measure the difference of sFlt-1, sEng, PIGF levels between EO-PE and LO-PE. This was an observational study with cross sectional design conducted at Dr. M. Djamil, TK Hospital. III dr. Reksodiwiryo and Biomedical Laboratory FK Unand Padang from August 2017 to August 2018. The sample of this study were 26 severe preeclampsia women : 13 (EO-PE)  and 13 (LO-PE), selected using consecutive sampling. Levels of sFlt-1, sEng, PIGF were examined using the enzyme-linked immunosorbent assay (ELISA) method. Statistical analysis was performed using unpaired t test and Mann-Whitney Test. Results shown that serum levels of sFlt-1 and sEng in (EO-PE)  were 9.51 ± 0.71 ng / L, 1.44 ± 0.06 ng / mL, 5.79 ± 0.42 ng / mL while in PEAL it was 8, 89 ± 0.78 ng / mL, 1.35 ± 0.14 ng / mL, 6.72 ± 0.76. There were a significant difference with a value of p <0.05. The conclusion of this study is that the levels of sFlt-1 and sEng are higher in (EO-PE)  than(LO-PE)and PIGF levels was lower in (EO-PE) compared to (LO-PE)